IMPORTANCE OF CONTINUING EDUCATION IN URGENCY AND EMERGENCY PRACTICES IN EMERGENCY CARE UNITS - Carolino de Abreu Alecrim, Tatiana; Douglas Soares de Albuquerque, Ewerton; de Lira Silva, Macerlane; Daniel Lucena de Santana, Jorge; Barros de Quental, Ocilma (Health and Society, 2025)
Continuing education plays a crucial role in enhancing the qualifications of healthcare professionals in Emergency Care Units (UPAs), fostering the ongoing development of the knowledge and skills necessary to handle urgent and emergency situations. This study reviewed the literature on the subject, highlighting benefits such as increased safety in interventions, reduced medical errors, and strengthened critical competencies like communication and decision-making under pressure. Educational technologies, including digital platforms and practical simulations, were also identified as effective tools for enhancing learning and addressing challenges related to time and resource limitations in UPAs. However, implementing continuing education programs faces significant barriers, such as financial constraints, resistance from professionals to adopt new practices, and the lack of structured institutional policies. Additionally, the high workload and staff turnover in UPAs hinder regular participation in training initiatives. These factors emphasize the need for strategies that integrate continuing education into routine care, ensuring sustainability and a positive impact on care quality. For future advancements, it is recommended to investigate the long-term impact of continuing education programs on care indicators, such as complication rates and patient satisfaction. The combination of hybrid methodologies, integrating digital resources and in-person activities, also deserves greater attention to overcome logistical limitations. Lastly, economic analyses of the costs and benefits of these programs can inform policy decisions and optimize investments in the field. Thus, continuing education establishes itself as an indispensable component for improving care in UPAs, ensuring quality and safety in service delivery.